The Titius-Bode law of planetary distances: its history and theory. - Nieto, Michael Martin (International series of monographs in natural philosophy, 1972)
The Titius-Bode Law of Planetary Distances: Its History and Theory is a 15-chapter book that first discusses the prehistory of the Law from Kepler to Kant. The next chapter details the formulation of the Titius-Bode Law. Subsequent chapters describe the Law's early successes and failures, early modifications of the Law, the Blagg-Richardson formulation, and the significance of the Law with respect to the origin of the solar system.